The Participation of Senior Citizens in Policy-Making: Patterning Initiatives in Europe - Falanga, Roberto (2021)
Worldwide, active aging policy calls for greater participation of senior citizens in the social, economic, and political realms. Despite emerging evidence of initiatives engaging senior citizens in social activities, little is known about the use of participatory approaches in the design and/or implementation of policies that matter to older citizens. This article identifies initiatives facilitating the civic participation of older people in policy-making in European Union member and associate states, drawing on a review of the literature, consultation of national policy experts, and exemplary case studies. Four main patterns of senior civic participation are identified: adopting consultative or co-decisional participatory approaches in policy design or policy implementation. The four are represented to varying degrees at different geographical levels (national, regional, local), with different actor configurations (appointed, elected/nominated, corporate representation), and with varying degree of institutionalization (temporary/permanent). Case studies illustrate approaches taken to enhance the quality and effectiveness of public services for senior citizens. Future research should strengthen this line of enquiry to cast further light on conditions facilitating the civic participation of senior citizens.